The impact of gender equality on education inequality: a global analysis based on GMM dynamic panel estimation - Baloch, Amdadullah; Mohd Noor, Zaleha; Habibullah, Muzafar Shah; Mhd Bani, Nor Yasmin (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Gender and education inequalities are a widespread phenomenon. This study investigates the impact of gender equality and its sub-indices on education inequality using panel data of 103 countries, over the period 2006-2014. Results reveal, by employing the System Generalize Method of Moment (Sys-GMM) estimation method, gender equality and its subindices of gender equality; health and survival, economic participation and opportunity and political empowerment gender equality exert a significant negative effect on education inequality, indicating that higher gender equality between males and females results in lower education inequality. GDP per capita, schooling and democracy have a negative and significant effect on education inequality. Conversely, unemployment, population density and dependency have a positive and significant impact on education distribution. Finally, the result implies that higher gender equality is the primary pathway to lower education inequality or achieving greater fairness in education access.